Trends in guideline implementation: an updated scoping review protocol. Issue 4 (16th April 2022) - Gagliardi, Anna R.; Malinowski, Jennifer; Munn, Zachary; Peters, Sanne; Senerth, Emily
ABSTRACT: Objective: The objective of this review is to assess trends in guideline implementation, including the interventions used, rationale provided, and the impact on patient or health care professional knowledge, behavior or outcomes. Introduction: Guidelines must be actively implemented to promote use and achieve beneficial outcomes. A review published in 2015 found that studies of guideline implementation did not employ a range of implementation planning approaches to select and tailor interventions, resulting in inconsistent impact. This study will update the 2015 review and elaborate beyond the four diseases originally covered to determine whether more recent efforts to implement guidelines are informed by best implementation practices. Inclusion criteria: We will include published studies that describe the implementation of guidelines on any clinical topic relevant to primary, secondary, or tertiary care using interventions targeted at patients, families/caregivers, or health care professionals. Methods: We will search MEDLINE, Embase, AMED, CINAHL, Scopus, and the Cochrane Library from 2014 (search date in 2015 review) to the present. Two or more reviewers will screen titles and full-text articles, and extract data from included studies. We will use summary statistics, tables, and a narrative summary to describe study characteristics, guideline implementation interventions, the rationale for intervention selection and tailoring (pre-identified barriers, patient or stakeholder preferences, theory), and intervention impact.